A taxonomic review of Rhabdocosma Meyrick (Lepidoptera, Ypsolophidae) with description of a new species from Japan. Issue 3 (July 2014) - Sohn, Jae‐Cheon; Gershenson, Zlata S.
Abstract: The Ypsolophid genus Rhabdocosma  Meyrick is reviewed. It comprises two known species: R. aglaophanes  Meyrick and R. dolini  Gershenson, and one new species from Japan, R. nematopogonites  Sohn, sp. nov. Photos of imagoes and male genitalia are provided for all three species of Rhadocosma . A close relationship between R. dolini and the new species, and its significance in the biogeography and world species diversity of Rhabdocosma, are discussed.